Kajian Efektivitas Metode Injeksi dan Metode Konvensional pada Penanganan Air Asam Tambang Berdasarkan Parameter pH dan TSS: Study of the Effectiveness of Injection Method and Conventional Method in Acid Mine Drainage Treatment Based on pH and TSS Parameters - Gita Lestari; Muhammad Ikrar Lagowa; Jarot Wiratama (MINERAL, 2026)
Acid mine drainage (AMD) is one of the major environmental challenges in coal mining activities and must be properly managed to prevent adverse environmental impacts. Based on the Decree of the Minister of Environment No. 113 of 2003, mining wastewater must have a pH value ranging from 6 to 9 and a maximum Total Suspended Solids (TSS) concentration of 400 mg/L. This study aims to compare the effectiveness of the injection method and the conventional method in treating acid mine drainage at PT Budi Gema Gempita based on pH and TSS parameters. The initial water quality showed a pH of 4.5 and a TSS concentration of 5,420 mg/L, indicating that it did not comply with the established environmental standards. The injection method utilized POWERBASE 3012, POWERCLEAR 1546, and POWERFLOC 4888, while the conventional method employed quicklime and aluminum sulfate (alum). The treatment results showed that the injection method achieved a final pH of 8.6 and a TSS concentration of 26 mg/L, whereas the conventional method resulted in a final pH of 7.2 and a TSS concentration of 1,899 mg/L. Both methods successfully increased the pH to meet the regulatory standard; however, only the injection method reduced TSS below the maximum allowable limit. Therefore, the injection method is considered more effective and has strong potential for sustainable implementation in acid mine drainage management at PT Budi Gema Gempita.